Dental Care Use Among Pregnant Women in the United States Reported in 1999 and 2002 - Peggy Timothé, DDS, MPH; Paul I. Eke, PhD, MPH, PhD; Scott M. Presson, DDS, MPH; Dolores M. Malvitz, DrPH (Centers for Disease Control and Prevention, 2005)
Introduction The purpose of this study was to determine national and state-specific estimates of dental care use among adult pregnant women in the United States using data from two 12-month periods. The study also determined person-level characteristics that may predict a lack of dental care use within this subgroup. Methods Responses were analyzed from 4619 pregnant women aged 18 to 44 years who participated in the 1999 and 2002 state-based Behavioral Risk Factor Surveillance System. Dental care use was defined as having a dental visit or a dental cleaning in the 12 months preceding the interview. State-specific estimates were adjusted to the 2000 U.S. population distribution. Multivariable regression analysis was used to evaluate person-level characteristics that may predict not obtaining dental care during this period. Results Overall, 70% of pregnant women in 1999 and 2002 had received dental care in the previous 12 months. Age-adjusted estimates ranged from 36% (Nevada) to 89% (Vermont) to 91% (Puerto Rico). In 19 states, 75% or more of pregnant women had obtained dental care in the previous 12 months (age-adjusted figure). Most pregnant women with dental care were non-Hispanic white and married, and they had a greater than high school education. Income and smoking status were significant predictors for not using dental care. Conclusion In several states, more than 70% of pregnant women reported a dental visit or dental cleaning during the previous 12 months. Relative to the general population, pregnant women are as likely to receive dental care, but certain subgroups need to do much better. However, these estimates may be biased toward a population with a higher socioeconomic status and may not represent dental care use among pregnant women in the general U.S. population.